Analyzing the Effects of Weather on Light Rail Transit Performance in Dublin, Ireland - O'Mahony, Margaret; Walsh, Gearoid (My University, 2022)
As climate change and greenhouse gas emissions receive increasing levels of attention, the need for sustainable transport solutions becomes increasingly apparent. The Luas is Dublin’s Light Rail Transit (LRT) network and, since completion in 2004, it has become key component of the city’s transport system, with plans for further expansion in the near future. Ensuring that sustainable transport options, such as the Luas, are attractive to users by providing a reliable service is a key step in increasing their usage and environmental benefits. This research investigates the effects of the weather on the reliability of the Luas trams, with a focus on identifying specific sections of the network and time periods that are increasingly vulnerable to weather-related disruption. A large dataset of Automatic Vehicle Location (AVL) data was received from Transport Infrastructure Ireland (TII) from which the required headways for the analysis were derived. Precipitation, air temperature and wind speed for the same time periods were obtained from the Irish weather service (Met Eireann). The two datasets were then combined and analysed using multiple linear regression. Precipitation was found to be the most influential weather variable for negative impacts on LRT performance. Unexpectedly, increases in wind speed resulted in decreases in headway times. Weather was found to have more substantial effects on the Luas Red Line than on the Green Line. The results of this study would be useful to transport authorities in their efforts to increase the resilience of the Luas network to adverse weather conditions.
Transportation Research Board Annual Meeting
Keywords: Weather; Light Rail Transit; Headways; Performance; Smart & Sustainable Planet; Environmental Impacts of Transport; Transport; extreme weather; Transport